Analisis Problematika Dan Strategi Adaptasi Akademik Serta Budaya Mahasiswa Pertukaran Internasional Di Universiti Muhammadiyah Malaysia - Hasibuan, Muhammad Basir; Andina, Dea Ananda; Rangkuti, Charles (Indonesian Research Journal on Education, 2026)
The international student exchange program at Universiti Muhammadiyah Malaysia (UMM) Perlis presents dual challenges of academic and cultural adaptation. This study aims to analyze these adaptation challenges and identify coping strategies employed by exchange students. Using a descriptive qualitative method with a phenomenological paradigm, data were extracted through the subjective experiences of key informants. The results revealed five main academic challenges: transition to a student-centered learning system, language barriers (technical terms and Malay dialect), high workload, difficulties with local references, and critical thinking standards. In the cultural dimension, obstacles were identified in the form of high-context communication, adjusting to food preferences, homesickness, barriers to relationships with local students, and differences in religious practices. Adaptation strategies developed included forming international study groups, proactively consulting with lecturers, using language apps, seeking comfort food, and maintaining digital family support. Analysis based on Berry's acculturation theory indicates that students tend to use an integration strategy, where they maintain their original identity while actively interacting with the local culture. Institutional support such as academic orientation and a buddy system were identified as crucial factors that need to be improved to optimize the adaptation process for international students in the future.